Pengaruh Kualitas Jasa Dan Harga Terhadap Keputusan Pembelian Tiket Angkutan Udara Sriwijaya Air Di Perwakilan Surakarta - Bartolomeus Herawan Mintardjo (Jurnal Pariwisata Indonesia, 2021)
The development of airlines that are owned or managed by private parties currently shows a fairly high development, so that the level of competition to get customers is getting more difficult. In line with this, it will be a challenge for the airline industry which is owned by the private sector and the government. One of the strategies adopted by both government and private airline owners in maintaining or increasing the number of customers is by providing quality services. The formulation of the problem in this research is how the effect of service quality is seen from five dimensions: tangibles, reliability, responsiveness, assurance, and empathy on the decision to purchase tickets for Sriwijaya Air flights. While the hypothesis of this research is that service quality has a significant influence on the decision to purchase tickets for Sriwijaya Air flights. This study aims to determine the effect of service quality (tangibles, reliability, responsiveness, assurance, and empathy) partially and simultaneously on customer ticket purchase decisions and to determine the more dominant influence of service quality (tangibles, reliability, responsiveness, assurance, and empathy) on the decision to purchase tickets for Sriwijaya Air flights. The theory used in this research is the theory of marketing management which is related to service quality. The approach used in this research is a survey and the type of research is descriptive quantitative. The research is explanatory. Data collection techniques by interview, circulating a list of questions to a sample of 91 respondents and study documentation. To test the hypothesis, multiple regression is used by performing the T test and the F test.